Michel Foucault and the tragic-existential form of freedom: toward an anarchic chiasm - Ramos Pérez, Gonzalo (Anales del Seminario de Historia de la Filosofía, 2025)
This article examines the early thought of Michel Foucault with the aim of elucidating the tragic-existential chiasm that shapes his initial conception of freedom, influenced by the ideas of Heidegger and Nietzsche. It analyzes how Foucault integrates the anti-essentialist readings of both philosophers to formulate a notion of freedom that shifts the question of the human being toward the margins of an anti-humanist hypothesis. This approach enables the development of a distinctive hermeneutics of freedom, which not only allows for an interpretation of Foucault's work through an anarchic lens but also positions his ethical-political thought within discussions on post-foundationalism, post-anarchism, and radical democracy. This article seeks to contribute to a deeper understanding of Foucault as an anarchic thinker, exploring some of the ideas that are deeply intertwined with philosophical debates aiming to exhaust the political language of modernity.
Keywords: Animality; Anti-Humanism; Heidegger; Nietzsche; Post-Anarchism; Post-Foundationalism